2021
DOI: 10.1101/2021.07.26.453903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D Convolutional Neural Networks for Classification of Alzheimer’s and Parkinson’s Disease with T1-Weighted Brain MRI

Abstract: Parkinson's disease (PD) and Alzheimer's disease (AD) are progressive neurodegenerative disorders that affect millions of people worldwide. In this work, we propose a deep learning approach to classify these diseases based on 3D T1-weighted brain MRI. We analyzed several datasets including the Parkinson's Progression Markers Initiative (PPMI), an independent dataset from the University of Pennsylvania School of Medicine (UPenn), the Alzheimer's Disease Neuroimaging Initiative (ADNI), and the Open Access Series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in this research are shown in Table 1 and Supplementary Table 4 . The original 28 studies were published between 2019 and 2022, with 27 of them from Asia ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) and one from North America ( Dhinagar et al, 2021 ). The study comprised a total of 6,057 participants, with 3,422 patients diagnosed with PD, 1,983 healthy controls, and 652 cases of APS (476 with MSA and 176 with PSP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Structural magnetic resonance imaging (MRI) based on standard anatomical T1-weighted (T1-w) is routinely used and accessible worldwide and does not subject the patient to ionizing radiation. In recent times with an increase in the available training data, deep learning and machine learning methods have shown great promise for various neuroimaging tasks such as brain age prediction, 3 diagnostic classification 4 and disease subtyping and staging, 5 based on detecting profiles of brain atrophy with T1-w MRI. In 2019, Wen et al 6 published a comprehensive review of over 30 papers that used convolutional neural networks (CNNs) for AD classification from anatomical MRI.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are several limitations in using CNN-based approaches for segmentation ( Ronneberger et al, 2015 ; Xue et al, 2018 ; Li et al, 2019 ; Rutherford et al, 2021 ). Although U-Nets can use skip connections to combine both low- and high-level features, there is no guarantee of spatial consistency in the final segmentation map, especially at the boundaries ( Isola et al, 2017 ; Yang et al, 2018 ; Zhao et al, 2018 ; Dhinagar et al, 2021 ). To address this limitation, methods that consider spatial correlations among neighboring pixels such as conditional random field and other graph cut techniques are used as post-processing refinement ( Pereira et al, 2016b ; Nancy, 2019 ; Son et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%